Put the Pressure on Your Cows for Performance - Jeffrey N. Carter (EDIS)
AN172, a 2-page fact sheet by Jeffrey Carter, describes how to routinely evaluate a beef cow herd, culling based on criteria for reproduction, functionality, and production. Includes a productivity outline of economically important traits of the cow. Published by the UF Department of Animal Science, July 2007.